2022
DOI: 10.1080/16549716.2022.2090123
|View full text |Cite
|
Sign up to set email alerts
|

The role of community health workers in influencing social connectedness using the household model: a qualitative case study from Malawi

Abstract: Background Community health workers (CHWs) play a vital role in facilitating social connectedness, building trust, decrease stigma, and link communities to essential healthcare and social support services. More studies are needed to understand the factors facilitating these interactions among CHWs, clients, and community members. Objective This study examined the CHW role and relationships between CHWs, communities, and health facilities that promote trust, positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… 1 Furthermore, by increasing health knowledge and healthcare-seeking behaviours, CHWs facilitate feelings of well-being and social connections, as supported in other recent CHW programme studies. 8 , 41 , 42 , 43 However, CHWs travel long distances on foot to reach households and sometimes do not have ways to help transport sick patients to the closest health facility. Previous studies have demonstrated that adequate scope, workload, and support are essential in empowering CHWs.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Furthermore, by increasing health knowledge and healthcare-seeking behaviours, CHWs facilitate feelings of well-being and social connections, as supported in other recent CHW programme studies. 8 , 41 , 42 , 43 However, CHWs travel long distances on foot to reach households and sometimes do not have ways to help transport sick patients to the closest health facility. Previous studies have demonstrated that adequate scope, workload, and support are essential in empowering CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns have previously been documented in a qualitative study in Malawi that describes stigma related to CHW interventions for infectious diseases or early pregnancies. 32 Findings from the Malawi study indicate that through the establishment of long-term relationships with CHWs, CHW associated stigma can be mitigated while care and treatment improve. Building on this study, we argue that challenges on acceptance of CHW services due to stigma or trust can be reduced through positive interpersonal, trust-based relationships between Community Members and CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…There are also barriers to patients accessing the services provided by CHWs. For example, a study in Malawi reported that individuals with HIV and tuberculosis experienced stigma and discrimination in their communities because CHW visits were associated with the presence of an HIV patient (10).…”
Section: Introductionmentioning
confidence: 99%